Effect of chromium (cr) particle size and span-20 surfactant on Aisi d2 hardened steel using electrical discharge machining - Jamil Hosni, Nor Ain (2020)
Existing manufacturing industries are facing challenges from modern advanced materials such as composite, super alloys, and hardened steels, which are hard and difficult to machine and process. Since it is not suitable to use conventional machining of the hard material, non-conventional machining such as electrical discharge machining (EDM) is one of the ideal techniques in dealing with these materials. However, the limitations of EDM will cause lower productivity and poor surface quality. Therefore, Powder Mixed Electrical Discharge Machining (PMEDM) has emerged as one of the advanced and innovative technique to eliminate the some of the disadvantages of EDM method. The fine powder particles are added into the tank then the spark gap is filled up with these additives particles. These electrically conductive powder particles reduce the insulating strength of dielectric fluid and increase the spark gap distance between tool electrode and workpiece, which due to this EDM process becomes more stable, thereby improving the EDM efficiency and quality of the machined surface. This research emphasizes the machining of AISI D2 hardened steel with EDM through adding both of micro and nano chromium powder mixed and span-20 surfactant using copper tool electrode. Then, machining productivity (i.e material removal rate (MRR), electrode wear rate (EWR) and surface roughness (Ra) and surface characteristics were investigated in terms of surface morphology, surface topography, recast layer thickness (RL) and microhardness. It was indicated that the addition of micro-nano chromium powder and span-20 surfactant to the dielectric notably enhanced the machining efficiency and better surface quality. The highest improvement 35~46 % of MRR, 29~69 % of Ra and 42~54 % of RL were attained at combination of micro-nano chromium powder and span-20 surfactant, respectively. There is no significant effect on EWR. For this purpose, full factorial 32 design of experiments (DOE) was chosen which consists of three levels of PMEDM parameters of chromium powder concentrations (Cp) and Span- 20 surfactant concentrations (Cs) for both micro and nano chromium powder. Response Surface Methodology (RSM) was utilized for responses optimization and Central Composite Design (CCD) was applied in designing the experiments to evaluate the effects of PMEDM parameters to three responses, MRR, EWR and Ra. Thus, this is clarify that the potential of addition of Cr powder and span-20 surfactant into dielectric fluid ability to gives a notable potential to be utilized as one of innovative technique, improving efficiency and better surface quality.